Anthropogenic microparticle ingestion by capelin (Mallotus villosus) in the Denmark Strait - Brawn, Caitlin Ellen, 1994- (2022)
Verkefni lokað til 31.05.2023 Plastic ingestion by marine fishes is a widely documented global environmental problem. However, this area of research has several deficiencies, including 1) data gaps on plastic ingestion in Arctic species, and 2) non-comparability and reproducibility of studies resulting from non-confirming methods and reporting standards. This thesis addresses these two data gaps by studying anthropogenic microparticle ingestion by East Greenland - Iceland - Jan Mayen capelin (Mallotus villosus) sampled in the Denmark Straight. Firstly, this study aimed to collect baseline anthropogenic microparticle ingestion in Icelandic capelin and investigate how ingestion relates to a series of biological variables. This was done by digesting 160 capelin gastrointestinal tracts (GIT) using 10% potassium hydroxide (KOH) and isolating anthropogenic microparticles using a 45 μm sieve. This study reports occurrence of 53.1%, a mean anthropogenic microparticle abundance of 1.37 ± 2.39 per individual, and no relationship between ingestion and biological variables of interest. Secondly, this study compared differences in time, material resources, procedural contamination, and data output between two anthropogenic microparticle isolation methods recommended in the microplastic harmonization literature. A 10% KOH digestion of capelin GITs was conducted on 319 were evenly divided and underwent a 45 μm sieving or 1.2 μm filtration protocol to isolate suspected anthropogenic microparticles. Both methods required similar material resources and resulted in equivalent procedural contamination; however, the sieving method took longer to conduct and the characteristics (ie, color, length, and morphology) of anthropogenic microparticle detected varied between methods. This study contributes to the growing body of knowledge on anthropogenic microparticle ingestion by Arctic species and provides a quantitative analysis of the differences between the two recommended methods, contributing to the discussion on the harmonization ...